Blockchain-enabled strategic optimization: A decision analytics framework for multinational enterprises’ e-commerce entry model - Liurui Deng; Xiaoying Hu; Ying Xiao (PLoS ONE, 2026)
With e-commerce booming, MNEs (Multinational Enterprises) often tap into online markets through E-retailers in multinational e-commerce platforms. Therefore, which e-commerce entry model MNEs choose can be critical, especially when the MNE owning a retail division in the same market. Notably, the MNE can address the plague of low-quality images of e-retailers by introducing blockchain technology, but the effectiveness of blockchain technology for quality verification also varies across different e-commerce entry models. In this paper, we develop a two-tier supply chain model with a manufacturing division in a high-tax area and various retailers in a low-tax area. The retailers comprise the manufacturing division of the MNE and e-retailers. The e-retailers include self-operated e-commerce, FBP merchants, i.e., merchants handling sales while the platform manages product delivery and after-sales services, and SOP merchants, i.e., merchants separately manage operations, shipping, and sales. We find that the larger the tax disparity, the lower the overall profits of MNEs, irrespective of the implementation of blockchain technology. Furthermore, the overall profit of the MNE is more significant when adopting a singular e-commerce entry model without the introduction of blockchain technology; conversely, the total profit of the MNE is more significant when adopting a composite e-commerce entry model with the introduction of blockchain technology. Interestingly, when blockchain technology is implemented, the MNE is more lucrative under the e-commerce entry model with a medium initial market potential if the service gap between the e-retailer and the manufacturing division is modest.